Pengaruh Kualitas Sumber Daya Manusia dan Karakteristik Usaha terhadap Kualitas Laporan Keuangan UKM Kabupaten Lumajang - Nur Fadilah (COSTING : Journal of Economic, Business and Accounting, 2019)
Small businesses are the backbone of the Indonesian economy. This research was conducted on Lumajang MSMEs. This study aims to determine the effect of four variables namely leadership education level (X1), accounting knowledge (X2), business size (X3) and length of business (X4) on the quality of financial statements. In this study data was collected by means of observations, interviews and questionnaires on 86 respondents, namely Lumajang MSME actors with purposive sampling technique, which aims to determine respondents' perceptions of each variable. The analysis used includes test data instruments (validity test, and reliability test), multiple linear regression analysis, classical assumption test (normality test, multicollinearity test, heteroscedasticity test), and hypothesis testing (F test, t test, coefficient of determination). From the results of the analysis using regression, it can be seen that the leadership education variable (X1), accounting knowledge (X2), business size (X3) and length of business (X4), all have a positive effect on the quality of financial statements. Keywords : Human Resource Quality, Business Characteristics, Financial Reports